2015
DOI: 10.1542/peds.2015-0608
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Cognitive Function Into Adulthood

Abstract: , Dieter Wolke, PhD, Dr rer nat hc a,d abstract BACKGROUND: Very preterm (VP; gestational age ,32 weeks) and very low birth weight (VLBW; ,1500 g) births are related to impaired cognitive function across the life span. It is not known how stable cognitive functions are from childhood to adulthood for VP/VLBW compared with term-born individuals and how early adult cognitive function can be predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
164
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 164 publications
(193 citation statements)
references
References 44 publications
19
164
2
8
Order By: Relevance
“…We found that VP/VLBW HRQL was more stable in the transition to adulthood than for controls. Similar higher stability over time has been reported for objective functioning such as IQ 30 indicating that life trajectories may be more fixed in preterm than term born populations.…”
Section: Tablesupporting
confidence: 71%
“…We found that VP/VLBW HRQL was more stable in the transition to adulthood than for controls. Similar higher stability over time has been reported for objective functioning such as IQ 30 indicating that life trajectories may be more fixed in preterm than term born populations.…”
Section: Tablesupporting
confidence: 71%
“…In comparison, VP/VLBW cognitive abilities measured as developmental quotient (DQ) in infancy may explain around 21% of VP/VLBW adult IQ. 12 Especially the presence of RDS, IVH, problems with mobility during the neonatal period, days of mechanical ventilation, less parenteral feeding, low/middle SES, and poor parent-infant relationship in the NICU and shortly after discharge were significant and unique predictors of adult cognitive abilities. These predictors can be routinely assessed in NICU's to identify VP/VLBW at risk of longterm adverse cognitive development.…”
Section: Discussionmentioning
confidence: 93%
“…Third, cognitive impairment was calculated as having an IQ score <2 SD of a recruited healthy term-born control group, born in the same hospitals and matched on variables such as sex and SES). 12 All analyses were repeated using logistic regression analyses to predict cognitive impairment including the construction of a receiver operating characteristic curve (ROC) to analyze whether combining information on the most important predictors would distinguish between VP/VLBW individuals with and without cognitive impairment in adulthood. As these results were comparable to predicting continuous IQ scores, they are only reported in online Supplement 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations